Cultural psychology and Deconstructing Developmental Psychology. (August 2015) - Crafter, Sarah
This paper looks at points of convergence and divergence between the different branches of cultural psychology and Burman's ideas in Deconstructing Developmental Psychology. The paper discusses the relationship between the developing ideas in cultural psychology over time and some of the shared theoretical and conceptual criticisms put forward in Deconstructing Developmental Psychology. This takes into account some of the differences between the symbolic approach, activity theory and an individualistic approach to cultural psychology. In turn, some of the bigger themes within the book are discussed, such as the role of 'normalisation' and demarcation of age, and studying the child in context and how these relate to the different account of cultural psychology and the influence these themes have had on the author's own work. Since this paper details a personal research journey, examples are taken from work on home–school mathematics education, child language brokering and young caring. Using these examples, the paper examines how cultural psychology is interested in the mediation between culture and the person, whilst Deconstructing Developmental Psychology asks us to question the stories and assumptions embedded within developmental psychology.